Studi komparatif kompetensi siswa sebelum dan sesudah penggunaan bahan ajar fluida bermuatan literasi saintifik dan HOTS pada kelas XI SMAN 10 Padang - Aini Syahbani; Hidayati Hidayati; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
In the 21st century the 2013 curriculum emphasizes learning. 2013 curriculum based learning should pay attention to the modern pedagogic dimension in physics learning, using a scientific approach. In fact, this learning has not been carried out maximally so that students critical thinking, motivation and problem solving skills are still in the low category. One solution to this problem is the physics of fluid instructional material containing scientific literacy and HOTS. The purpose of this study was determining the differences in student’s competencies before and after using fluid instructional materials containing scientific literacy and HOTS in grade XI of SMAN 10 Padang. The type of research conducted is a quasi-experimental with one group pretest-posttest design. The population in this study were all class XI students of SMAN 10 Padang academic year 2018/2019. The sample in the study was class XI MIPA 1 which was obtained by purposive sampling technique. The research instrument was in the form of a written test for knowledge competencies, observation sheets for attitude competencies and scientific performance assessments for skills competencies. Analysis of the data used was descriptive statistical test analysis and analysis of comparative tests correlated for competency attitudes, knowledge, and skills. The results of this study are that the use of fluid instructional materials with scientific literacy and HOTS gives a difference to the competency of students before and after class XI of SMAN 10 Padang with a confidence level of 95%. Thus, the use of fluid instructional materials provides a meaningful influence on student competencies including competency attitudes, knowledge, and skills.